THE MANUFACTURING PRODUCTS AND PARTS BY 3D-PRINTING METHOD FROM COMPOSITE FILAMENTS WITH HIGH METAL CONTENT - POLISHCHUK, Oleg; POLISHCHUK, Andrii; LISEVICH, Svitlana; ZALIZETSKYI, Anatoliy; MELNYK, Vasiliy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
It is established that one of the most promising areas of development of modern engineering is the development of new technologies for rapid production (rapid manufacturing), the essence of which is the layered design of powder products based on CAD model, ie model whose three-dimensional geometry is described digitally by using solid modeling programs (AutoCAD, SolidWorks, Compas-3D, CATIA, ProE, etc.). The main advantages of using additive technologies, including 3D printing with filaments containing metals. The types of 3D printers that print metal are considered. The use of metal powders in 3D printing technologies is described. The main characteristics and properties of such metals, TI titanium, stainless steel SS, aluminum Al, copper Cu, FE iron and alloys based on them can be used as materials or additives in additive technologies. The advantages of their use over traditional technologies (casting, rolling, etc.) are described. The scheme of technological process of manufacturing products of industry mechanical engineering by a 3D printing with a high metal content is given. Each of the stages of the technological process is considered and described. Stainless steel metal powder was selected for the manufacture of filament and its chemical composition is investigated. Experimental studies have been conducted to determine the mechanical, thermophysical and rheological characteristics of polymeric materials used for the manufacture of 3D prints. On the basis of the studies, it is proposed to use Plastic powder as a connecting element in the filament. The design of the auger for supplying the material of the extrusion machine is designed and manufactured. The form of the extrusion head is developed and selected, which sets the diameter of the filament being made. A 3D printer for printing products and parts with a high metal content was selected and improved. Experimental studies of the wear of the 3D printer’s extruder nozzle on contact with the abrasive thread.